An analytical survey of pleonasm occurrence in the Holy Quran - hamed dehghani firouzabadi; ali Rad (مطالعات زبانی و بلاغی)
One of the most important and effective aspects of Linguistic miracles of the Holy Quran is its accuracy in choosing suitable words in this godly book and hidden mysteries in the selection of each letters and terms. One of the subordinates of these subjects is the subject of inexistence of redundancy of vocabularies and after that the inexistence of pleonasm in the Holy Quran. In this article, after definition of the term pleonasm in Rhetoric, and a quick look at the background of the subject of inexistence of redundancy in the Holy Quran, we will proceed to a comparative discussion about the inexistence of redundancy and excessive use of words in this Holy book. According to this, we have tried to show a little bit of the punctuality of the Allah’s word in its Linguistic use by paying attention to some verses of the Holy Quran in which some interpreters hold to have redundancy. Throughout the survey, the backgrounds of redundancy in the Holy Quran are as: the syntagmatic of seemingly synonymous words, the syntagmatic of interdependent words, the expression of axioms, the reference of common and proper nouns on each other and the recurrence of a single term.